2020
DOI: 10.1038/s41598-020-74184-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors predicting final visual outcome in quiescent proliferative diabetic retinopathy

Abstract: To investigate factors reflecting visual outcome and macular perfusion in quiescent proliferative diabetic retinopathy (PDR) patients after panretinal photocoagulation (PRP). We included 118 patients with quiescent PDR who had completed PRP. All participants had standardized interview to determine ocular history, smoking status, cardiovascular risk factors, and history of diabetic mellitus (DM). Foveal avascular zone (FAZ) area, retinal vessel density (VD) and vessel length density (VLD) were measured using op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
2
4
0
Order By: Relevance
“…However, in the case of severe retinal ischemia, diffusion of oxygen needed by macular may remain insufficient and even lead to macular edema in spite of PRP, causing lower vision [ 15 , 30 ]. This finding is also in line with the study that lower vision is associated with the larger avascular zone area of foveal in DR patients [ 31 ]. Therefore, prevention of DR-worsening may be an important strategy to reduce DR-related vision loss, even blindness.…”
Section: Discussionsupporting
confidence: 93%
“…However, in the case of severe retinal ischemia, diffusion of oxygen needed by macular may remain insufficient and even lead to macular edema in spite of PRP, causing lower vision [ 15 , 30 ]. This finding is also in line with the study that lower vision is associated with the larger avascular zone area of foveal in DR patients [ 31 ]. Therefore, prevention of DR-worsening may be an important strategy to reduce DR-related vision loss, even blindness.…”
Section: Discussionsupporting
confidence: 93%
“…However, in cases where the macular ischemic condition presenting as low visual acuity is severe, diffusion of oxygen may remain insufficient despite PRP, and DR could actually worsen. In particular, this finding in line with the result of a study that reported that low visual acuity is associated with larger foveal avascular zone size in patients with DR 10 . Poor visual acuity can imply macular ischemia, which is likely to be associated with a progression of DR.…”
Section: Discussionsupporting
confidence: 90%
“…Among the systemic parameters VD was significantly correlated with HbA1c, which is in agreement with previous studies. [ 33 34 ]…”
Section: Discussionmentioning
confidence: 99%